Decitabine improves MMS-induced retinal photoreceptor cell damage by targeting DNMT3A and DNMT3B - Ji, Yanli; Zhao, Meng; Qiao, Xiaomeng; Peng, Guang-Hua (Frontiers in Molecular Neuroscience, 2023)
Introduction Retinitis pigmentosa (RP) is a group of neurodegenerative retinopathies causing blindness due to progressive and irreversible photoreceptor cell death. The alkylating agent methyl methanesulfonate (MMS) can induce selective photoreceptor cell death, which is used to establish RP animal models. MMS induces DNA base damage by adding alkyl groups to DNA, and epigenetic modifications influence DNA damage response. Here, we aimed to explore the relationship between DNA methylation and DNA damage response in dying photoreceptors of RP. Methods The mouse RP model was established by a single intraperitoneal injection of MMS. The retinal structure and function were assessed by H&E, OCT, TUNEL, and ERG at several time points. The expression of DNA methylation regulators was assessed by qPCR and Western blot. DNMT inhibitor 5-aza-dC was applied to inhibit the activity of DNA methyltransferases and improve the retinal photoreceptor damage. Results The outer nuclear layer (ONL) and IS/OS layer were significantly thinner and the retinal function was impaired after MMS treatment. The cell death was mainly located in the ONL. The retinal damage induced by MMS was accompanied by hyperexpression of DNMT3A/3B. The application of DNMT inhibitor 5-aza-dC could suppress the expression level of DNMT3A/3B, resulting in the remission of MMS-induced photoreceptor cell damage. The ONL and IS/OS layers were thicker than that of the control group, and the retinal function was partially restored. This protective effect of 5-aza-dC was associated with the down-regulated expression of DNMT3A/3B. Conclusion These findings identified a functional role of DNMT3A/3B in MMS-induced photoreceptor cell damage and provided novel evidence to support DNMTs as potential therapeutic targets in retinal degenerative diseases. Graphical Abstract